11B NMR Together with Infrared Spectroscopy Provides Insight into Structural Elucidation of Quadrivalent Diazaborines & Cyclic Boronate Esters: Intriguing & Little-Explored - Ashley L. Dey (Molecules, 2024)
Imidazo-fused diazaborines, which serve as intermediary structures somewhat alongside benzene and borazine, had been of particular interest to Dewar and Snyder more than 60 years ago. To this end, Dewar utilised his ‘<semantics>π</semantics>-complex theory’so as to represent ‘borazaros’as a ‘quadrivalent’ species; however, sadly, modern representations have deviated and leapt into ‘trivalent’ counterparts. Bonding in boron species has never been straightforward, to such an extent that the orthodox ‘ethane’ like diborane, i.e., H3B–BH3, which conformed to the paradigmatic rules of molecular structure, in particular, hybridisation and electronegativity, was later evolved to a more realistic ‘3-centre 2-electron’ bonding so as to give the lie to the purported diborane structures of X-ray diffractors. Herein 11B NMR together with IR spectroscopy sheds light on the nature of bonding in borazaros, and ‘caged’ cyclic oxazaborons so as to reinforce, and reinvigorate the old literature, which could be of interest to both the synthetic, and medicinal chemist alike.